PENGARUH INSENTIF DAN PEMANTAUAN : DAMPAK TERHADAP ORIENTASI KEUANGAN DAN NON-KEUANGAN DALAM PENGANGGARAN MODAL - Savika Wulandari; Grace Tianna Solovida (Jurnal Penelitian Ekonomi dan Bisnis, 2019)
This research aimed to investigate the influence of incentive and monitoring provided to the decision maker that impacted on finance and non-finance orientation in budget planning. The independent variable in this study was incentive and monitoring in budget planning focusing on the project recommendation selection. While the dependent variable was finance and non-finance orientation in budget planning. The research employed an experimental method using descriptive statistics analysis applying a case study approach. The analysis involved multinomial logistics regression using a statistics computer application. The result of this study indicated that the decision maker did not provide significant evidence that s/he made a high emphasis on the finance and non-finance orientation without incentive and monitoring. However, the decision maker receiving private incentive emphasized highly on cash inflows and a low emphasis on cash outflows, or vice versa.Â Keywords: budget planning, project selection, finance orientation, non-finance orientation, private incentive, monitoring.